Mathematical modeling of reverse atom transfer radical polymerization in miniemulsion - Zurman, Ayelen (2018)
In this work, we study the reverse atom transfer radical polymerization in miniemulsion using a water-soluble initiator. This study is motivated by the technological advantages of performing polymerizations in dispersed systems, and the attractive possibilities of controlled radical polymerization techniques to produce tailor made polymers. A mathematical model for this system is presented. The model predicts average molecular properties as well as the full molecular weight distribution (MWD) for different experimental conditions. The method of moments is applied for calculating average properties and the probability generating function (pgf) technique is used to model the MWD. The model is based on the mass balance equations of In this work, we study the reverse atom transfer radical polymerization in miniemulsion using a water-soluble initiator. This study is motivated by the technological advantages of performing polymerizations in dispersed systems, and the attractive possibilities of controlled radical polymerization techniques to produce tailor made polymers. A mathematical model for this system is presented. The model predicts average molecular properties as well as the full molecular weight distribution (MWD) for different experimental conditions. The method of moments is applied for calculating average properties and the probability generating function (pgf) technique is used to model the MWD. The model is based on the mass balance equations of the reacting species. It takes into account the reactions in both the aqueous and organic phases and the mass transfer between them. Predicted conversions, average molecular weights, polydispersity indexes and MWDs for different experimental conditions agree well with experimental data reported in the literature. reacting species. It takes into account the reactions in both the aqueous and organic phases and the mass transfer between them. Predicted conversions, average molecular weights, polydispersity indexes and MWDs for different experimental conditions agree well with experimental data reported in the literature.